Adsorption of Cu (II) and Cd (II) from aqueous solutions by chitosan immobilized in alginate beads. Issue 4 (August 2020) - Kuczajowska-Zadrożna, Małgorzata; Filipkowska, Urszula; Jóźwiak, Tomasz
Graphical abstract: Highlights: The higher amount of active groups responsible for metals binding in ALG−CHs. Increase in the range of pH at which it exhibited a high efficiency of metals removal in ALG−CHs. ALG−CHs seems to be a very promising biosorbent for the removal of heavy metals. The Sips model is suitable for the description of metals sorption onto CHs and ALG−CHs. Abstract: A new sorbent – chitosan immobilised in alginate (ALG-CHz) was used as an adsorbent for the Cd 2+ and Cu 2+ heavy metal ions removal from aqueous solutions. The research has shown, that in case of the new sorbent the pH of the solution does not affect the adsorption effectiveness of either the Cd 2+ as well as Cu 2+ ions, what widens the possibilities of its use. For the determination of maximum sorption capacity of the tested sorbent the Sips model was used. It has shown the best fit to the experimental data, determined based on the ARE value. The values of the sorption capacities calculated from the model were 527.3 mg/g d.m for Cu 2+ and 207.0 mg/g d.m. for Cd 2+ .